Effects of tramadol and acepromazine on intraocular pressure and pupil diameter in young healthy cats - Schroder,Deise Cristine (2018)
ABSTRACT: This study aimed to investigate the effects of the systemic administration of acepromazine, tramadol and the association of both on intraocular pressure (IOP) and pupil diameter (PD) in young healthy cats. Cats were randomly allocated into three groups (n=10/each) and intramuscular acepromazine (AG), tramadol (TG) or acepromazine combined with tramadol (ATG) were injected. PD (electronic caliper) and IOP (applanation tonometry) were assessed before (baseline) and following 15, 30, 60, and 120 minutes of treatments. It was verified that in AG, PD decreased significantly from time point 30 to 120 (P=0.002), but such reduction did not differ significantly from baseline (P=0.89). In TG, PD increased significantly from the first 15 minutes, until the last time point of evaluation (P<0.001). In ATG, PD increased significantly from time point 30 to 120 when compared to baseline (P<0.001); but significant differences from time point 30 to 120 were not seen (P=0.71). Comparisons among groups showed that PD values of TG and ATG were significantly higher than that of AG (P<0.05). IOP values, on the other hand, did not change significantly among time points and groups (P>0.05). It can be concluded that tramadol alone or in association with acepromazine produced significant mydriasis for up to 120 minutes, without changing IOP values in normal cats. Results of this study suggested that tramadol alone or in association with acepromazine caused significant mydriasis and did not change IOP values in normal cats. Therefore, it may be considered a satisfactory pre-anesthetic combination for ophthalmic surgery in cats. However, further studies are warranted on the use of such protocols in cats with ophthalmic diseases undergoing ocular or intraocular surgery.